The Influence of Work Discipline and Training on Teacher Performance at Public Elementary School 064983 Medan - Delima Sarah Panjaitan; Dwi Fany Fransiska Dewi Butar Butar; Hafni Cholida Nasution (CV. INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: The optimization of teacher performance constitutes a fundamental determinant in achieving educational excellence within primary educational institutions. Despite the acknowledged importance of work discipline and professional training, empirical evidence concerning their concurrent influence on teacher performance in Indonesian elementary schools remains insufficiently documented. This investigation endeavored to ascertain the magnitude and significance of the relationship between work discipline and training on teacher performance at SD Negeri 064983 Medan, examining both individual and combined effects. Materials and methods: A quantitative research paradigm employing census sampling methodology was implemented, encompassing the complete population of 30 civil servant teachers. Data acquisition was executed through validated questionnaires utilizing a five-point Likert scale. Multiple linear regression analysis was conducted using SPSS version 22.0, accompanied by comprehensive assumption testing including normality, multicollinearity, and heteroscedasticity assessments. Results: The analytical procedures yielded statistically significant relationships for both predictor variables. Work discipline demonstrated a substantial positive influence (β = 0.632, t = 6.118, p < 0.001), while training exhibited a moderate positive effect (β = 0.260, t = 2.611, p = 0.015). The combined model manifested robust explanatory power (F = 53.823, p < 0.001, R² = 0.785), accounting for 78.5% of the variance in teacher performance. Conclusions: The empirical evidence substantiates that both work discipline and training exert statistically significant positive influences on teacher performance, with work discipline demonstrating comparatively greater predictive strength. The findings underscore the imperative for educational administrators to systematically enhance disciplinary enforcement mechanisms and implement comprehensive professional development programs to optimize pedagogical effectiveness.